Adaptive finite-time stabilisation of a class of high-order nonlinear systems with inverse dynamics. Issue 11 (18th August 2017) - Huang, Shipei; Xiang, Zhengrong
ABSTRACT: This paper investigates the adaptive finite-time stabilisation of a class of high-order nonlinear systems with inverse dynamics and time-varying control coefficients. Under the assumptions that the inverse dynamics of the subsystem are input-to-state stable, and nonlinear terms depend upon the inverse dynamics, the states and unknown parameters, we present a systematic design procedure for an adaptive finite-time state-feedback control law by using a recursive design approach. It is shown that under the proposed adaptive control law, the state of the closed-loop system is finite-time convergent. Two examples are provided to show the effectiveness of the proposed method.